Females Are More Sensitive to Opponent’s Emotional Feedback: Evidence From Event-Related Potentials - Chen, Xuhai; Yuan, Hang; Zheng, Tingting; Chang, Yingchao; Luo, Yangmei (Frontiers in Human Neuroscience, 2018)
It is widely believed that females outperformed males in emotional information processing. The present study tested whether the female superiority in emotional information processing exists in a naturalistic social-emotional context, if so, what the temporal dynamics underlies. The behavioral and electrophysiological responses were recorded while participants were performing an interpersonal gambling game with opponents’ facial emotions given as feedback. The results yielded that emotional cues modulated the influence of monetary feedback on outcome valuation. Critically, this modulation was more conspicuous in females: opponents’ angry expressions increased females' risky tendency and decreased the amplitude of RewP and feedback P300. These findings indicate that females are more sensitive to emotional expressions in real interpersonal interactions, which is manifested in both early motivational salience detection and late conscious cognitive appraisal stages of feedback processing.